Ócio e trabalho redesenhando significados na longevidade - Lima, Maria Amélia Ximenes Correia (2011)
This thesis is an analysis of the concept of occupation, with the main foundation of Occupational Science, Occupational Therapy and Anthropology. The proof of its importance to the health and well-being is the foundation for a careful examination of the leisure class, through its historical and its models proposed by scholars of the subject, making clear its importance as a meaningful occupation for old age. The work is presented in the world longevity due to financial need or for the pleasure of staying in the game. The difficulty of managing their free time after retirement is one of the challenges inherent in aging. As a result the time and boredom apper as evils in longevity. The experiense of leisure is identified as personal development for the elderly. The redesign of leisure and work emerge as elements of redefinition of old age